INNER CORE ANISOTROPY, ANOMALIES IN THE TIME-AVERAGED PALEOMAGNETIC FIELD, AND POLARITY TRANSITION PATHS - Clement B.M.; Stixrude L. (My University, 1995)
The diffusion of the dynamo-generated magnetic field into the electrically conducting inner core of the Earth may provide an explanation for several problematic aspects of long-term geomagnetic field behavior. We present a simple model which illustrates how an induced magnetization in the inner core which changes on diffusive timescales can provide a biasing field which could produce the observed anomalies in the time-averaged field and polarity reversals. The Earth's inner core exhibits an anisotropy in seismic velocities which can be explained by a preferred orientation of a polycrystalline aggregate of hexagonal close-packed (hcp) iron, an elastically anisotropic phase. Room temperature analogs of hcp iron also exhibit a strong anisotropy of magnetic susceptibility, ranging from 15 to 40% anistropy. At inner core conditions the magnetic susceptibility of hcp iron is estimated to be between 10-4 and 10-3 SI. We speculate here that the anisotropy in magnetic susceptibility in the inner core could produce the observed anomalies in the time-averaged paleomagnetic field, polarity asymmetry, and recurring transitional virtual geomagnetic pole (VGP) positions.